A study on efficacy of high fluence Q-switched neodymium doped yttrium aluminium garnet laser in macular amyloidosis - Kaur, Jasleen; Kaur, Tanreet (International Journal of Research in Dermatology, 2020)
Background: Macular amyloidosis (MA) typically presents as small, dusky-brown or greyish pigmented macules, treatment of which remains challenging with topical and systemic therapies, however Q-switched neodymium-doped yttrium aluminium garnet (Nd:YAG) laser has proven to be an effective treatment modality to reduce hyperpigmentation. The aim of the study is to study the efficacy of Nd:YAG laser in the management of MA. Methods: 30 female patients were treated with Q-switched Nd:YAG laser at 1064 nm with a spot size of 3 mm at a fluence of 6-7 J/cm2, frequency of 2 Hz, for 350-500 pulses. Total number of pulses decreased with each treatment session as the intensity of the hyperpigmentation decreased. The procedure was repeated at one-month intervals for a total of 6 treatment sessions. Results: After completion of treatment sessions with Nd-YAG laser 36.66% patients showed >50% improvement in the pigmentation. 66.6% patients were satisfied with the laser treatment. 33.3% patients showed <25% improvement and unsatisfied with the treatment. Conclusion: MA remains an enigma and a source of concern for the suffering patients and physicians. Q-switched Nd-YAG laser 1064 nm has shown positive response in the reduction of pigmentation in MA.